Hmm. It appears that f(x) = √(x-2), so
(f•g)(x) = f(x)•g(x) = √(x-2) • (6x-7)
Maybe you meant
(f◦g)(x) = f(g(x)) = √(g-2) = √(6x-9)
How did you arrive at your answer?
Find (f • g) when f(x)=√x-2 and g(x)= 6x-7
I got √-11x+14
4 answers
I did this
F(6x-7)
√x-2(6x-7)
√x-12x+4
√-11x+14
F(6x-7)
√x-2(6x-7)
√x-12x+4
√-11x+14
√x-2(6x-7) = √x-2g
mighty weird, I must say.
Better read up on the distributive property and composition and multiplication of functions.
mighty weird, I must say.
Better read up on the distributive property and composition and multiplication of functions.
So the answer is √x-2g ?